Murine supraspinatus tendon injury model to identify the cellular origins of rotator cuff healing. (1st November 2016) - Yoshida, Ryu; Alaee, Farhang; Dyrna, Felix; Kronenberg, Mark S.; Maye, Peter; Kalajzic, Ivo; Rowe, David W.; Mazzocca, Augustus D.; Dyment, Nathaniel A.
ABSTRACT: Purpose of this study : To elucidate the origin of cell populations that contribute to rotator cuff healing, we developed a mouse surgical model where a full-thickness, central detachment is created in the supraspinatus. Materials and methods : Three different inducible Cre transgenic mice with Ai9-tdTomato reporter expression (PRG4-9, αSMA-9, and AGC-9) were used to label different cell populations in the shoulder. The defect was created surgically in the supraspinatus. The mice were injected with tamoxifen at surgery to label the cells and sacrificed at 1, 2, and 5 weeks postoperatively. Frozen sections were fluorescently imaged then stained with Toluidine Blue and re-imaged. Results : Three notable changes were apparent postoperatively. (1) A long thin layer of tissue formed on the bursal side overlying the supraspinatus tendon. (2) The tendon proximal to the defect initially became hypercellular and disorganized. (3) The distal stump at the insertion underwent minimal remodeling. In the uninjured shoulder, tdTomato expression was seen in the tendon midsubstance and paratenon cell on the bursal side in PRG4-9, in paratenon, blood vessels, and periosteum of acromion in SMA-9, and in articular cartilage, unmineralized fibrocartilage of supraspinatus enthesis, and acromioclavicular joint in AGC-9 mice. In the injured PRG4-9 and SMA-9 mice, the healing tissues contained an abundant number of tdTomato+ cells, while minimal contribution of tdTomato+ cells was seen in AGC-9 mice. Conclusions : The study supports the importance of the bursal side of the tendon to rotator cuff healing and PRG4 and αSMA may be markers for these progenitor cells.